STUDY OF FOREIGN EXPERIENCE IN IMPROVING TAX ADMINISTRATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Based on the experiences of the world, the experiences of different states are studied in order for tax policy to optimize them and adapt to the modern conditions of world governance. The successful implementation of these approaches makes it possible to objectively assess the available financial resources necessary for the implementation of priority approaches.